Los valores como eje transversal en el proceso de enseñanza aprendizaje en los alumnos del noveno año de básica del Colegio Nacional Juan Montalvo de la ciudad de Machala periodo lectivo 2012-2013. - Palacios Ramos, Eddy Antonio (2015)
This research raises the possibility of using human values with the family as an alternative learning to empower our students from the school, relationship with parents, students and teachers, as well as to transmit properly understanding one person to another person. In the family, the appropriate communication patterns strengthen relationships and family ties, inadequate communication patterns away and isolate their members.